1999
DOI: 10.1111/j.1346-8138.1999.tb02100.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Generalized Morphea with a High Titer of Anti‐Borrelia burgdorferi Antibodies

Abstract: A 69-year-old male had noticed pruritus on the back for the previous 3-4 years and cutaneous sclerosis with swelling of the dorsum of the neck had developed in the last one and a half years. However, he had never complained of Raynaud's phenomenon of the fingers, dry mouth, or dry eyes. At this first visit to our hospital, he complained of erythematous cutaneous sclerosis with swelling of the dorsum of the neck. Histopathological findings biopsied from the neck showed epidermal hyperplasia with elongation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Similarly, in six patients with LMCS, such a relationship could not be found. It is not always possible to differentiate LMCS and PRS on a clinical basis, and there is controversy as to whether they are part of the same spectrum or represent different entities . However, our patients' clinical diagnosis was supported by histopathological criteria applied to translesional biopsies, thus allowing clear differentiation between diseases.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, in six patients with LMCS, such a relationship could not be found. It is not always possible to differentiate LMCS and PRS on a clinical basis, and there is controversy as to whether they are part of the same spectrum or represent different entities . However, our patients' clinical diagnosis was supported by histopathological criteria applied to translesional biopsies, thus allowing clear differentiation between diseases.…”
Section: Discussionmentioning
confidence: 93%
“…Most published studies have been performed in smaller groups or on a retrospective basis . Ever since a possible relation between Borrelia and morphea was suggested, contradictory results have failed to demonstrate a relation to the spirochete …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrelia burgdorferi (Bb) has been implicated in generalized morphea [25]. Additionally, an earlier study found 38% of seropositive (n=5) and 23% of seronegative (n=26) patients with morphea exhibited elevated B.burgdorferi induced lymphocyte proliferation, supporting a causal role, at least for some patients with morphea [26].…”
Section: Introductionmentioning
confidence: 87%
“…[109] Other localized sceleroderma represents undetected B. burgdorferi infectrials have confirmed both promising results and high treatmenttion. [130][131][132][133][134] related mortality. Stem cell transplantation continues to be evalu-…”
Section: Cardiac Diseasementioning
confidence: 99%